Usability of the Department of Education's learning modules in Science 9 - Martinez, Rosalie B (2024.)
Modular instruction is an alternative instructional design that uses developed instructional materials which are based on the needs of the students. Students are encouraged to work on various activities that are interesting and challenging to maintain focus and attention. This descriptive mixed method study is primarily aimed at determining the usability of the learning module in Science 9 for the first quarter as assessed by the respondents from six public secondary schools in the District of Hamtic, Schools division of Antique, for school year 2023-2024. The study was conducted in February to April 2024 among Grade 10 students in the six public secondary schools in the said District. In all, 304 Grade 10 students were selected as study respondents. The researcher utilized systematic random sampling technique in the selection of the respondents. The validated researcher-made Checklist on the Usability of the Learning Module in Science 9 was used to gather data. Statistical tools used to interpret the data were frequency, percentage, mean, and standard deviation for descriptive analysis and t-Test and One-Way Analysis of Variance (ANOVA) for inferential analysis. Significance level for all inferential data was set at alpha 0.05 at two-tailed test. The qualitative data were gathered using a FGD Interview Guide. The study concluded that the DepEd's Learning Module in Science 9 for the first quarter is highly usable whether the respondents are taken as an entire group or classified into sex, Family monthly income, home learning support providers, technology support, school population and home distance to school. No significant differences existed in the respondents' evaluation of the said learning modules when the respondents are classified into the variables considered for this study. Results from the FGD affirm that the respondents find the subject learning module in view of the simple terminologies used, accessible references and physical make-up. However, the participants would still prefer to use books over learning modules. The researcher presented recommendations for further improvement of the Science 9 Learning Module for the first quarter.
Special Problem (M.Ed. - Biology) -- [Miagao, Iloilo] : University of the Philippines Visayas, July 2024.